Setup of an electron probe micro analyzer for highest resolution radioscopy - Hanke, R.; Nachtrab, Frank; Burtzlaff, S.; Voland, V.; Uhlmann, N.; Porsch, F.; Johansson, W. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2009)
Structural investigation and characterization of objects below the micrometer-scale level often require either big efforts in experimental setup and critical time schedules as is the case with synchrotron sources or a big effort in test object preparation including destructive methods (e.g. grinding) for the investigation within an electron microscope. The limiting factor for high-resolution imaging with conventional X-ray sources is the focal spot size of the X-ray tube used. Focal spot sizes down to 500 nm can be achieved with double-focusing X-ray tubes and transmission targets. To be able to use X-ray transmission imaging for structural investigation with highest resolution in everybody's laboratory, we modified an electron probe micro analyzer (EPMA) to be used as an X-ray source. With this it is possible to obtain electron beam diameters below 200 nm and to produce X-rays using a special transmission target. Due to the low X-ray intensity and in order to profit from the high magnification, a high-resolution, low-noise detector is to be used. We chose a Medipix2 detector for that purpose. We will present the setup and first results of radioscopic images with a resolution of about 240 nm.
EAM Import::2019-03-13